1846 Mich. Rev. Stat. 692, §16. - (:unkn) unknown (General Publisher, 1846)
If any person shall go armed with a dirk, dagger, sword, pistol or other offensive and dangerous weapon, without reasonable cause to fear an assault or other injury, or violence to his person, or to his family or property, he may, on complaint of any person having reasonable cause to fear an injury or breach of the peace, be required to find sureties for keeping the peace, for a term not exceeding six months, with the right of appealing as before provided.
--
Keywords: SURETY